DIGITAL MARKETING KEKINIAN BAGI UMKM KRIWAKZ KERIPIK IKAN WADER RAWA SALATIGA - Widaryanti Widaryanti; Luhgiatno Luhgiatno; Maduretno Widowati (Buletin Abdi Masyarakat, 2021)
Swamp wader chips are one of the snacks or snacks made from wader fish. The nutritional content of swamp wader fish is very high, this can be used as an alternative to providing nutritious food at affordable prices for all people. Some of the wader swamp iwak chips businesses are still on the scale of home industries or micro, small and medium enterprises (MSMEs). One of the SMEs that sells wader swamp fish chips is the SMEs "Kriwakz". The production process is still done traditionally. The selling price of Kriwakz chips has not carefully calculated the cost of production. Packaging of wader Kriwakz fish chips using a sealer adhesive manually. The existence of the covid 19 pandemic is a blessing for Kriwakz SMEs because the demand for Kriwakz chips has increased sharply. Consumers prefer to make purchases online, so buyers of Kriwakz chips are spread from Sabang to Merauke. Kriwakz SMEs require understanding and training on digital marketing in the creation of social media content. The first priority solution is to facilitate Kriwakz SMEs in making digital marketing, training content creation to be uploaded on social media Facebook and Instagram. Second, the procurement of automatic packing tools to overcome the speed of sales service to consumers. The outputs of this PKMS are an increase in sales turnover, an increase in product quantity, an increase in understanding and digital marketing skills of Kriwakz SMEs. Keywords: Swamp Wader Fish Chips, Digital Marketing, Automated Packing Tool, Sales Increase